Evaluation of four regimens of methyl aminolevulinate mediated by red light to treat actinic keratoses: A randomized controlled clinical protocol - Ricardo Hideyoshi Kitamura; Milene Alves Azevedo; Joao Paulo Ratto Tempestini; Christiane Pavani; Lara Jansiski Motta; Sandra Kalil Bussadori; Ellen Sayuri Ando-Suguimoto; Kristianne Porta Santos Fernandes; Raquel Agnelli Mesquita-Ferrari; Cinthya Cosme Gutierrez Duran; Anna Carolina Ratto Tempestini Horliana (PLoS ONE, 2025)
The multifocality of actinic keratosis (AK), the unpredictability of lesion evolution with potential progression to squamous cell carcinoma (SCC), and the consequent risk of local extension and metastasis, alongside the recent development of new therapies, make the selection of a therapeutic regimen challenging. The increasing incidence of this condition is associated with economic costs and its impact on quality of life, which has fostered interest in studying protocols for treating this skin condition. The topical application of 16% methyl aminolevulinate (MAL) is well-established in the literature for its local therapeutic effects and ease of application. However, the high cost of medication, long incubation time, and adverse effects such as itching and burning in some patients limit the dissemination of this treatment. Studies are needed to test other protocols of this promising therapy to increase acceptance among patients and professionals. Therefore, the objective of this protocol is to compare the efficacy of the topical application of MAL at concentrations of 8% and 16%, mediated by red light, as well as to evaluate the impact of different incubation times (1 or 3 hours) in the treatment of actinic keratoses on the face, with a 6-month follow-up. This parallel-arm, 6-month follow-up randomized controlled, double-blind clinical protocol will consist of 4 groups: G1 - Control Group - MAL 16% irradiated with 643 nm and 75 J/cm2 and 3-hour incubation time (n = 36), G2 - MAL 16% and 1-hour incubation (n = 36), G3 - MAL 8% - 3 hours (n = 36), and G4 - MAL 8% - 1 hour (n = 36). The primary outcome will be the complete remission of the lesion at six months. Secondary outcomes will include treatment success (75% reduction in the initial number of lesions), recurrence rate, emergence of SCC, incidence of adverse effects, and improvement in skin texture, wrinkles, and pigmentation using a validated scale. All outcomes will be assessed at 30 days, 3, and 6 months. At six months, quality of life will be assessed using the Actinic Keratosis Quality of Life questionnaire (AKQoL) and Face-Q. If data are normal, they will be subjected to 3-way ANOVA and presented as means ± standard deviation (SD). Otherwise, they will be presented as median and interquartile range and compared using the Kruskall-Wallis and Friedman tests. Categorical variables will be evaluated with the chi-square, Fisher’s exact, or likelihood ratio tests. A p-value < 0.05 will be considered significant.